2013
DOI: 10.1101/gad.207654.112
|View full text |Cite
|
Sign up to set email alerts
|

Translational profiling of hypocretin neurons identifies candidate molecules for sleep regulation

Abstract: Hypocretin (orexin; Hcrt)-containing neurons of the hypothalamus are essential for the normal regulation of sleep and wake behaviors and have been implicated in feeding, anxiety, depression, and reward. The absence of these neurons causes narcolepsy in humans and model organisms. However, little is known about the molecular phenotype of these cells; previous attempts at comprehensive profiling had only limited sensitivity or were inaccurate. We generated a Hcrt translating ribosome affinity purification (bacTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 55 publications
9
112
2
Order By: Relevance
“…All the mouse cell type-specific gene expression profiling experiments were conducted on a single platform, most using published translating ribosome affinity purification (TRAP) data [GEO: GSE13379 (Doyle et al, 2008);GSE30626 (Dougherty et al, 2012); GSE38668 (Dalal et al, 2013);and GSE36068 (Dougherty et al, 2013], and habenula data [GSE43164 (Görlich et al, 2013)], except for retinal cell data (Corbo et al, 2007). Cell-specific gene lists for the cell types ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the mouse cell type-specific gene expression profiling experiments were conducted on a single platform, most using published translating ribosome affinity purification (TRAP) data [GEO: GSE13379 (Doyle et al, 2008);GSE30626 (Dougherty et al, 2012); GSE38668 (Dalal et al, 2013);and GSE36068 (Dougherty et al, 2013], and habenula data [GSE43164 (Görlich et al, 2013)], except for retinal cell data (Corbo et al, 2007). Cell-specific gene lists for the cell types ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To test this approach, we combined our analysis with a transcriptomic study of narcolepsy (Honda et al, 2009). Narcolepsy can be caused by a loss of Hcrt-expressing neurons (Peyron et al, 2000), which we have profiled (Dalal et al, 2013). Microarray data from mice where these neurons have been ablated identified 63 downregulated genes, which were sufficient to specifically indicate a loss of Hcrt neurons (Fig.…”
Section: Csea Of Transcriptome Data In Narcolepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the importance of the Hcrt system, little is known about the developmental processes that give rise to Hcrt neurons. A recent study found that mice lacking the LIM domain homeobox transcription factor Lhx9 had fewer Hcrt neurons (Dalal et al, 2013), suggesting that Lhx9 is required to specify a subset of Hcrt neurons. However, overexpression of Lhx9 in adult mice or in a mouse neuroblastoma cell line had no effect on Hcrt cell number or expression.…”
Section: Introductionmentioning
confidence: 99%